The Phenomenon Of Postpartum Blues In Primiparas (Mothers With The Birth Of The First Baby) - Setyaningrum, Dyah Titi; Metra, Litra Amanda; Sukmawati, Viradevi Eka (Jurnal Kesehatan Mahardika, 2023)
Mothers who have given birth for the first time (primiparas) are prone to experiencing postpartum blues. Postpartum blues are often overlooked so they can develop into serious mental disorders. An in-depth understanding of this phenomenon is deemed necessary to be able to recognize this phase well so that later it can develop more appropriate treatment. The purpose of this study was to provide an overview of the experiences and appreciation of postpartum blues in primiparas. This research is a descriptive phenomenological study using three primiparous participants by conducting in-depth interviews using the free directive interview technique. In this study, the results obtained that the postpartum blues was caused by physical exhaustion, unwanted pregnancy, the postpartum recovery process, and the lack of family support, especially spouse. This condition makes it difficult for mothers to control their emotions, negative thoughts and behaviors, and trauma to have the next child. Doing fun activities, putting the baby in day care or actively returning to work was reported as a way to relieve symptoms of postpartum blues.